AI vs. Human in Screenwriting: Is AI the Future Screenwriter? - Kemal Çelik (Sakarya İletişim, 2024)
This research paper investigates the challenge of discerning between content generated by humans and AI language models across various screenwriting elements. The study presents loglines, treatments, synopses, and dialogue examples to a group of 24 participants. These script elements are created by one human scriptwriter and an AI model. The participants are persons who have taken scenario courses, selected by purposive sampling method. The AI model used to generate the script content is Bing Chat, which is powered by ChatGPT 4, a conversational neural network known for its ability to produce natural and coherent text. Both AI-generated and human-created screenplay elements were provided to the participants, who were then asked questions related to them. The method of presenting both human and AI-generated screenplay options to each participant was chosen because it allows for a direct comparison and an accurate measure of the participants' ability to distinguish between the two. The structured interview type, which is also known as standard interview and researcher-managed interview, was used in this study. The average accuracy rate for all the script elements was 52.7%, which means that the participants had a moderate level of success in identifying the AI-generated and human-generated script elements. The study shows that artificial intelligence can produce script elements that are comparable to, and sometimes even preferred over, human-generated ones.